Professional Android 2 application development - Meier, Reto 1978- (Wrox professional guides., 2010)
Provides information on using Android 2 to build and enhance mobile applications, covering such topics as creating user interfaces, using intents, databases, creating and controlling services, creating app widgets, playing audio and video, telphony, and using sensors.--Source other than Library of Congress